2008
DOI: 10.1021/ar700111a
|View full text |Cite
|
Sign up to set email alerts
|

Density Functionals with Broad Applicability in Chemistry

Abstract: Although density functional theory is widely used in the computational chemistry community, the most popular density functional, B3LYP, has some serious shortcomings: (i) it is better for main-group chemistry than for transition metals; (ii) it systematically underestimates reaction barrier heights; (iii) it is inaccurate for interactions dominated by medium-range correlation energy, such as van der Waals attraction, aromatic-aromatic stacking, and alkane isomerization energies. We have developed a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

129
5,461
3
45

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 7,169 publications
(5,638 citation statements)
references
References 82 publications
129
5,461
3
45
Order By: Relevance
“…[48][49][50] In equation 1, HL stands for the high level chosen to obtain the corrected estimation of the activation free energy. In our case M06-2X/6-31+G(d,p) 34,35 has been used. HL calculations are carried out under the effect of the field created by the MM environment, where the electrostatic coupling between the QM and MM subsystems is calculated using point charges on the QM atoms.…”
Section: Free Energy Calculationsmentioning
confidence: 99%
“…[48][49][50] In equation 1, HL stands for the high level chosen to obtain the corrected estimation of the activation free energy. In our case M06-2X/6-31+G(d,p) 34,35 has been used. HL calculations are carried out under the effect of the field created by the MM environment, where the electrostatic coupling between the QM and MM subsystems is calculated using point charges on the QM atoms.…”
Section: Free Energy Calculationsmentioning
confidence: 99%
“…Quantum chemical calculations were carried out by means of the B3LYP 49,50 and M05-2X [41][42][43][44][45][46][47][48] hybrid functionals. Full geometrical optimizations using the 6-31G(d) basis set were carried out with the Gaussian 03 package.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Thus, a methyl 60 group in the oxazoline ring (ligand 10a') is enough to model the reaction experimentally carried out with 10a and 10b, but a bulkier tert-butyl group is necessary to account for the experimental behavior of 10c and 10d (ligand 10c' bearing a methyl group gives worse results). From the methodological 65 point of view, single-point energy calculations using the M05-2X functional [41][42][43][44][45][46][47][48] carried out on B3LYP 49,50 optimized geometries led to much better relative energies, which is necessary to account for the subtle energy differences involved in enantioselective processes. It has been reported that the hybrid meta functional M05-2X shows a superior 5 performance with respect to classical functional in the field of transition metal thermochemistry, which is of particular interest in our theoretical study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where the first term in the right-hand side of equation (2) the HL energies where obtained at the M06/6-31+G* level 24,25 of theory using Gaussian09. 26 The selected QM configurations were obtained along the AM1/MM minimum energy path traced down from the transition structure to the product and reactant valleys.…”
Section: Methodsmentioning
confidence: 99%